Pengaruh pemahaman technology acceptance model dan pemahaman etika profesi akuntan terhadap komitmen menjadi akuntan profesional dengan penguasaan teknologi informasi sebagai variabel moderating - Khalisah Visiana Subekti; Sahiddah Sahidah (Universitas 17 Agustus 1945 Jakarta, 2022)
Currently the world is entering an era of revolution where there are a lot of developments in various fields including information technology and the economy seen from all sectors of work that are already using more sophisticated technology, there are various technologies that are used to help make work easier today, just as an accountant has many using computers to help make their work easier as well as various uncertainties faced by companies are factors that encourage companies to invest in information technology. Likewise in the field of accounting, information technology is very important in supporting the process of making financial reports. One of the qualified accounting application programs. Technology also helps an accountant obtain a variety of information that can be used. When viewed from technology acceptance, it describes how users accept and adopt certain technologies. One of the most prominent is the Technology Acceptance Model (TAM) as a form of acceptance of information technology in the world of accountants.